Effect of Extraction of Mesioangularly Impacted Mandibular Third Molars on the Periodontal Status of Adjacent Second Molars: A Retrospective Observational Study - Yang Liu; Jiuqing Lu; Yichao Shen; Lei Zhen; Jiapeng Wang (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: The Mandibular Third Molar (M3M), often the last tooth to erupt, is commonly impacted due to insufficient space in the dental arch, leading to various oral health complications such as pericoronitis, infections, root resorption, cysts, and tumours. Notably, mesioangular impaction is the most prevalent type and is closely associated with the caries and periodontal issues of the Mandibular Second Molar (M2M). Periodontal diseases are significant contributors to tooth loss in adults, and the absence of M2M poses challenges for restoration while increasing the burden on remaining teeth. Aim: To evaluate the effect of extracting mesioangularly impacted M3M on the periodontal status of M2M. Materials and Methods: A retrospective observational study with pre- and post-comparisons was conducted at Tongji Hospital, affiliated with Tongji University, Shanghai, China, from October 2024 to February 2025. A total of 56 patients were included. Periodontal parameters, including Probing Depth (PD) and Bleeding On Probing (BOP), were evaluated before and after tooth extraction. Statistical analyses were performed using paired comparisons with the Wilcoxon signed-rank test, group comparisons with the Mann-Whitney U test and the KruskalWallis test, and unpaired t-test and Welch’s Analysis of Variance (ANOVA) where appropriate. A p-value of